1997
DOI: 10.1046/j.1365-2796.1997.131151000.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of weight loss during treatment with d‐fenfluramine

Abstract: Abstract. Toornvliet AC,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have typically been conducted in only 50 ± 100 patients followed for 3 ± 12 months. 1,10,13,14,16,19 Our study showed that only body weight, treatment group and, to a lesser extent, age predicted weight loss and weight maintenance outcome and that the power of the prediction was quite low as only 7 ± 8% of the variation in weight change could be accounted for by these predictors. Using BMI did essentially not increase the predictive power, probably due to the high correlation between body weight and BMI in this population of subjects.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies have typically been conducted in only 50 ± 100 patients followed for 3 ± 12 months. 1,10,13,14,16,19 Our study showed that only body weight, treatment group and, to a lesser extent, age predicted weight loss and weight maintenance outcome and that the power of the prediction was quite low as only 7 ± 8% of the variation in weight change could be accounted for by these predictors. Using BMI did essentially not increase the predictive power, probably due to the high correlation between body weight and BMI in this population of subjects.…”
Section: Discussionmentioning
confidence: 57%
“…2 In other studies, no statistically signi®cant correlation between weight loss and initial bodyweight was found. 1,13 This could, at least partly, be explained by the relatively small number of subjects included in the studies and the duration of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a low brain 5-HT level is associated with enhanced appetite (Leibowitz et al, 1987) and impaired impulse control in rats (Bizot, Le Bihan, Puech, Hamon, & Thiebot, 1999) and in humans at risk for alcoholism (Crean, Richards, & de Wit, 2002; LeMarquand, Benkelfat, Pihl, Palmour, & Young, 1999). Among obese humans, many medications that enhance serotonergic function induce weight loss (Hanotin, Thomas, Jones, Leutenegger, & Drouin, 1998; Pijl et al, 1991; Strain, Strain, & Zumoff, 1985; Toornvliet, Pijl, Hopman, Westendorp, & Meinders, 1997; Wadden et al, 2005), and reduce caloric intake (McTavish & Heel, 1992; Pijl et al, 1991; Wurtman et al, 1981) (although it should be noted that some serotonergic agents with prominent anticholinergic and antihistaminic action cause weight gain) (Ruetsch, Viala, Bardou, Martin, & Vacheron, 2005). Whether 5-HT plays a role in inhibitory control of eating in overweight individuals, specifically, has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate or sensitive predictors would be useful in selecting an appropriate treatment regimen for individual obese patients. Earlier studies suggest that a positive family history [1], repeated weight loss in the past and extreme body dissatisfaction were important factors in predicting weight loss [2]. Higher pretreatment body weight [3], resting metabolic rate (RMR), fat‐cell hyperplasia and upper body‐fat distribution [4] were associated with greater weight losses.…”
Section: Introductionmentioning
confidence: 99%